Public Financial Management and Its Emerging Architecture - Cangiano, M. (International Monetary Fund, 2013)
The first two decades of the twenty-first century have witnessed an influx of innovations and reforms in public financial management. The current wave of reforms is markedly different from those in the past, owing to the sheer number of innovations, their widespread adoption, and the sense that they add up to a fundamental change in the way governments manage public money. This book takes stock of the most important innovations that have emerged over the past two decades.